2017
DOI: 10.1101/lm.045948.117
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor GluA1 subunit is implicated in capsaicin induced modulation of amygdala LTP but not LTD

Abstract: Capsaicin has been shown to modulate synaptic plasticity in various brain regions including the amygdala. Whereas in the lateral amygdala the modulatory effect of capsaicin on long-term potentiation (LA-LTP) is mediated by TRPV1 channels, we have recently shown that capsaicin-induced enhancement of long term depression (LA-LTD) is mediated by TRPM1 receptors. However, the underlying mechanism by which capsaicin modulates synaptic plasticity is poorly understood. In the present study, we investigate the modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 51 publications
2
15
2
Order By: Relevance
“…We have recently extended these findings by showing that transcriptional changes can also be detected after a long-term memory can no longer be recalled (Perez, Patel, Rivota, Calin-jageman, & Calin-Jageman, 2018). Specifically, we used microarray and qPCR to identify changes in gene expression that accompany forgetting of a long-term sensitization memory in Aplysia californica .…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…We have recently extended these findings by showing that transcriptional changes can also be detected after a long-term memory can no longer be recalled (Perez, Patel, Rivota, Calin-jageman, & Calin-Jageman, 2018). Specifically, we used microarray and qPCR to identify changes in gene expression that accompany forgetting of a long-term sensitization memory in Aplysia californica .…”
Section: Introductionmentioning
confidence: 78%
“…We have previously shown that savings memory is apparent 7 days after sensitization training, a time point at which recall has become impossible for most animals (Perez et al, 2018). Here we sought to determine if savings memory persists even longer, testing 14 days after training (protocol in Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations